Zinc-induced hypocupremia and pancytopenia, from zinc supplementation to its toxicity, a case report - Ahsan Wahab; Kamran Mushtaq; Aqsa Khan; Muhammad Shahzeb Khan Khakwani; Adeel Masood; Jeremey Henderson; Faizan Malik (Greater Baltimore Medical Center, 2021)
According to one estimate, zinc supplementation is widely used in the USA by almost 37% of the elderly population above age 71. Zinc has perceived benefits of immune system enhancement without realizing the harmful effects when used in excess. One of its under-recognized side effects is hypocupremia or copper deficiency due to excessive gastrointestinal losses as excessive zinc in the gut competes with copper for absorption. If severe, hypocupremia can cause hematologic changes (anemia, leukopenia/neutropenia, thrombocytopenia, and pancytopenia) with and without neurological deficits. Since zinc-induced hypocupremia is an overlooked entity, there is a lag of 12 months between the onset of symptoms and diagnosis. Most patients usually undergo a series of costly and sometimes invasive tests such as bone marrow biopsies during this lag time. Once diagnosed, the treatment is as simple as discontinuation of zinc and oral copper supplements. Here, we present a case report of zinc-induced hypocupremia and pancytopenia in an 81-year-old lady who was taking zinc supplements for macular degeneration. The patient presented with leukopenia with neutropenia, thrombocytopenia, and moderate anemia. This case report aims to educate clinicians since this is an easily missed entity and likely more prevalent than known due to widely used zinc supplementation.